Perbandingan Model Kinetika Hidrolisa Enzimatis Sabut Kelapa - Rudy Agustriyanto (Seminar Nasional Teknik Kimia Kejuangan, 2015)
This article will show a comparison of the reaction kinetics model of enzymatic batch hydrolysis of coconut coir. This reaction is required as one of the stages in the conversion process of lignocellulosic biomass into alternative fuels. Kinetics model plays an important role in explaining the performance and characteristics of the process. Kinetics model can easily be used to control and predict the properties of the process. Kinetics data was obtained from laboratory experiments enzymatic hydrolysis reaction batch of coconut coir by pretreatment using dilute NaOH solution. Profile data will be modeled by first order dynamic model and the results will be compared to power model